(untitled) (Journal of the College of Basic Education, 2022)
This study was done to find out the impact of offer and marketing methods in eggshells of local and imported table eggs that available in Baghdad markets. For this purpose collected 50 samples of table eggs and microbial tests were conducted that included total counts of aerobic bacteria, coliform, Staphylococcus Spp., molds and yeasts and Salmonella Spp.. The results showed there is a big difference in the counts of microbiology on Eggshells between summer and winter where has greatly increased those counts in summer the percentage of Salmonella reached to 6% in summer and 1% in winter, and the process of eggs washing before packing clear effect in reducing the counts of all kinds of microbiology under consideration the ratio Salmonella in unwashed eggs reached to 4% While not presence in the washed eggs, and it was to the offer method a significant impact in the numbers of microbiology with the highest counts for all kinds of bacteria in eggshells that displayed in cartoon open dishes and the closed cartoon dishes came in second degree while the closed plastic dishes were at least in the counts of microbiology, and the percentage of Salmonella in the three modalities of the offer was 4% , 2% and 0 %, respectively .